Psikoedukasi untuk Meningkatkan Pemahaman Orang Tua Terkait Anak Slow Learner (Studi Kasus Anak TK): Penelitian - Luthfiana May Sarah; Suri Mutia Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Children with slow learner characteristics are often experience learning difficulties that require special support from their environment, especially their parents. This article aims to describe the implementation of psychoeducation for parents in managing preschool children diagnosed with slow learner. This research is a case study of a 6-year-old boy at Kindergarten X. The assessment process involved interviews, observations, and intelligence tests using WPPSI to identify the child's cognitive functions and learning difficulties. The intervention consisted of structured psychoeducation sessions designed to improve parents' understanding of their child's condition and appropriate learning strategies. This intervention was evaluated by looking at changes in pre- and post-test scores. The results of the intervention showed an increase in pre- and post-test scores, which means that parents' knowledge about the characteristics of slow learners, learning needs, and effective learning strategies has increased. This study highlights the importance of psychoeducation as an evidence-based approach to empowering parents and facilitating optimal development for children with slow learning characteristics.